Moderated Mediation Effect of Fear of Covid-19 and Organizational Trust on The Relationship Between Perceived Organizational Support and Helping Co-Workers During The Pandemic: A Study On Health Professionals - Oğuz Demirel; Fuat Yalman (Cumhuriyet Üniversitesi İktisadi ve İdari Bilimler Dergisi)
In this study, firstly, the mediating role of organizational trust in perceived organizational support and helping co-workers was examined. Next, the moderating role of COVID-19 fear on organizational trust and helping co-workers was tested. The study was performed on 401 health professionals working in public hospitals in Turkey. The data were collected through questionnaire and were analyzed by structural equation modeling and hierarchical regression technique. According to the findings of the study, perceived organizational support has a positive and significant effect on helping co-workers. In addition, organizational trust has a full mediating effect on this relationship. Finally, the moderating role of COVID-19 fear on the relationship between organizational trust and helping co-workers has not been established.